Knowledge, Attitude and Practice on Smoking Among Students and Staff in Universiti Putra Malaysia - Md. Numan, Sharker (2005)
The aim of this study was to determine the prevalence of smoking and factors associated with smoking and to determine the knowledge, attitudes, practices on antismoking measures related to smoking among students and staff of Universiti Putra Malaysia (UPM), Serdang, Selangor, Malaysia. A cross-sectional study design was used. A multistage stratified proportionate to size sampling technique was used to select the sample. The list of students and staff of UPM served as sampling frame. The total population for this study was 28053. Sample size was 2364 and was computed using EPI - INFO. Data was collected from 5th July to 27" August 2004 using a structured pre-tested questionnaire. The response rate was 85%. Out of the 2008 respondents, 60% were female, 62.8% Malay and 67.2% were Muslims. The overall prevalence of ever and current smokers amongst students and staff was 13.7% and 9.9%, respectively. The prevalence of ever and current smokers among male was 30% and 21.8%; and for the female was 2.8% and 2%. The prevalence of ever and current smokers among students was 12.1% and 8.9%; and staff was 26% and 17.7%, respectively. The mean initiation age of smoking was 16.7 + SD 3.7 years and it was lowest among Malays (16.3 years) and diploma level students (15 years). Prevalence of current smokers was high among Indians (12.7%) and Malays (1 1.6%) ethnic groups; and, Hindus (13%) and Muslim (1 1.9%) religious groups. Technicians had the highest (31.8%) current smoking prevalence at the UPM. Just for fim (54.2%) was the main reason for starting smoking and residence (45.1%) was the favourite place for smoking. Amongst current smokers, 63.9% had low level of addiction to nicotine. The prevalence of smoking was associated with age, economic status, race, religious, family and peer groups smoking habits. Most students and staff had good knowledge on the health risk of smoking. Never smokers had better knowledge on hazards of smoking and more positive attitudes. In conclusion, UPM smoking prevalence is low as compared to the national prevalence. However, it still constitutes a problem among university students and staff in UPM, in spite of their knowledge of its hazards, attitude and practices. There is a need to implement an anti-smoking program for university students and staff.